Something Old, Something New, Something Borrowed, Something Blue: Aspects of Interdisciplinary Knowledge Transfer from a Translation Studies Perspective - Mara Götz (Forum, 2012)
This article sets out to investigate points of contact and pathways of interdisciplinary knowledge diffusion from a translation studies point of view. For this purpose, notions of innovation, memes, aspects of idea transmission, sociological network theories, and diffusion of knowledge in networks are discussed against the backdrop of network studies theories from the discipline of sociology.